Using Macroscopic, Microscopic, and FTIR Spectroscopy combined with Chemometrics to Authenticate Arabica Coffee from Antbush - Fernando, David; Santosa, Djoko; Rohman, Abdul (Majalah Obat Tradisional, 2024)
Limited coffee stocks, high consumption, export demands, and increasing prices may contribute to counterfeiting. In other countries, including India and Africa, coffee forgery using antbush has been extensively established. Due to its abundance in Indonesia, unscrupulous coffee growers allegedly employ antbush (Senna occidentalis) as an adulterant in coffee to increase commercial earnings. This study aims to authenticate coffee from antbush using macroscopic and microscopic differences and FTIR spectroscopy combined with chemometrics. The arabica coffee samples from various regions were oven-roasted to a second crack and milled. The materials were then examined under macroscopic, microscopic, and infrared spectroscopic conditions. The obtained responses were used to monitor the qualitative and quantitative information in the targeted samples. Antbush in coffee samples is successfully identified microscopically by remnants of palisade tissue as well as the structural differences of the endosperm. In addition, FTIR spectroscopy combined with multivariate calibration can accurately estimate the concentration of antbush as adulterants in the target sample. Principle component regression (PCR) provides the best modeling for the relationship between the actual value. FTIR predicted the value of antbush with the lowest RMSEC and RMSEP values of 0.852 and 0.896, respectively, with the coefficient of determination (R2) in calibration and validation models of 0.9996 and 0.9967, respectively. The combination of macroscopic, microscopic, and FTIR spectroscopy offered reliable tools to authenticate arabica coffee from antbush.